Melatonin: it's expamding universe - Martín Giménez, Virna Margarita (2023)
Dr. Russel J. Reiter was awarded his fifth honorary title by the National University ofCuyo, Argentina, for his exemplary contributions towards unraveling the mysteries of thepineal gland and, importantly, its major secretory product, melatonin. This commentaryprovides a glimpse of his accomplishments and a summary of his speech during theceremony.